(untitled) (The Pakistan Development Review, 2015)
Economists agree that human capital is an important determinant of economic growth [Arrow (1962); Aghion and Howitt (1992)]. Human capital-led growth generally concludes the positive impact of the two with the help of existing developed theories and empirical evidences. Nonetheless, the standard empirical result of a direct relationship between human capital (however measured) and economic growth, has been criticised on several fronts. First, the impact of other growth-related factors like quality of education, health of the labour force, inflation, corruption, unemployment, rule of law, etc. should not be ignored. These endogenous characteristics of a country are included in Becker‘s (1993) definition of human capital. In addition, as noted by Abramovitz (1986), social capabilities are important in the adoption and diffusion of technologies but countries differ in social capabilities. Therefore, to the extent to which human capital contributes to economic growth through innovation, its effect is conditioned by the country‘s social capabilities which include factors like quality of institutions and governance.